Two new genera of Phoridae (Insecta: Diptera) from the Neotropical Region - Brown, Brian V.; Kung, Giar-Ann (Zootaxa, 2004)
Two new genera and species, Tapantia bicasa and Tayrona nitifrons, are described from Tapanti National Park, Costa Rica, and Tayrona National Park, Colombia, respectively. Tapantia bicasa is a basal lineage phorid of uncertain relationships, as it structurally resembles the genus Triphleba Rondani, but has male terminalia extremely similar to those of Dohrniphora Dahl. Tayrona nitifrons is highly unusual in many aspects, but especially in frontal setation, leg structure, wing structure, and male terminalia. It is classified in the subfamily Metopininae, although its precise relationships are unknown.